Electrospun carbon fibers for microbial fuel cells: A novel bioanode design applied to wastewater treatment. (20th March 2021) - Sanchez, Jérémie-Luc; Pinto, David; Laberty-Robert, Christel
Highlight: · Electrospun carbon nanofibers are explored as a potential electrode material for bioanodes. · ECNs bioanodes exhibit significantly good performances (221 W·m -3 & 0.95·10 3 A·m -3 ). · This bioanode design was successfully used to produce electrical power from a wastewater anolyte. Abstract: Electrospun carbon nanofibers (CNFs) are explored as a potential electrode material for bioanodes due to the advantages of a high specific surface area (surface area per volume), a good conductivity and an architecture and surface adapted to the electroactive bacteria colonization. These electrodes are colonized by exoelectrogenic strains – either the model bacterium Shewanella oneidensis or a wastewater-occurring bacterial consortium and are then integrated into a lab-scaled setup. Its electricity output is then screened using a synthetic anolyte or actual wastewaters as a fuel. Overall, electrospun carbon bioanode-based MFCs using a lactate-based synthetic anolyte and a potassium ferricyanide catholyte exhibited significantly better performances (221 W·m -3 & 0.95·10 3 A·m -3 ) than their counterpart made of commercial control carbon felt. Moreover, this bioanode design was successfully used to produce electrical power from a wastewater anolyte (438 W·m -3 & 4.4·10 3 A·m -3 ). These performances were reached even without any further bioreactor internal resistance optimization, demonstrating their promising application for wastewater-based electricity generation. Graphical abstract: Image, graphical abstract